Prevalence of Rape Myths and Sexual Double Standards Among University Students in Pakistan - Jamshed, Nida (Journal of interpersonal violence, 2021)
This study aimed to determine the prevalence of rape myths and sexual double standards among Pakistani university students. The sample size was 500 university students. The results indicated that 76.8 % students had more belief in rape myths, while 23.2 % had less belief on rape myths. In total, 71.4% had less sexual double standards, while 28.6 % had more sexual double standards. Furthermore, results showed that men believed more in rape myths as compared with women. Young adults of age ranging from 17 to 24 years had high sexual double standards as compared with adults of the age range of 25 to 32 years. Moreover, findings of focus group discussions (FGDs) highlighted that rape myths and sexual double standards are highly prevalent. The study revealed that Pakistani students are gender biased, as power and authority are associated with men. They also shared that rape victims in Pakistan do not get any support from family; rather, in most cases, the rape victims are killed in the name of so-called honor to maintain the reputation of family in society.